The Effect of Klika Ongkea Extract (Mezzetia parviflora Becc.) on Pancreatic β-Cells Regeneration by Streptozotocin-Induced in Wistar Rats - Jangga - Jangga; Mansur - Mansur; Saparuddin - Latu (The Journal of Pure and Applied Chemistry Research, 2022)
This study aimed to determine the effect of Klika ongkea (Mezzetia parviflora Becc.) extract on the regeneration of pancreatic β-cells on Wistar rats that were induced using streptozotocin. Streptozotocin (STZ) with a 40 mg/kg BW dose was used in this study. Eighty adult male Wistar rats were used for this study. The animals were divided into four groups, Group I, as a healthy controls; Group II as an STZ-induced, Group III, STZ-induced and treated with galvus (Vildagliptin) 0.9 mg/200 g BW; Group IV, STZ-induced and treated with Klika ongkea 100 mg/kg BW. This study was conducted for 28 days. Four animals each group on the 1st, 7th, 14th, 21st and 28th days were observed to analyze the number of pancreatic β-cells. On the last day, pancreases were isolated and stained with hematoxylin & eosin (H&E) to analyze the regeneration of pancreatic β-cells. The data analysis was performed using an Independent-Sample T-Test to compare the number of pancreatic β-cells. The results showed that the administration of Klika ongkea extracts affected the pancreatic β-cells regeneration. These findings suggest that Klika ongkea has an effect on the regeneration of pancreatic β-cells in streptozotocin-induced rats.